Clinical Usefulness of IgE as a Serological Marker for Diagnosis of Nodular Scabies in Diyala Province - Ibrahim, Khudir khalaf; Ali, Ali Ibrahim; Mohammad, Burug (Diyala Journal of Medicine, 2019)
This study designed to evaluate the clinical usefulness of IgE as a serological marker for diagnosis of nodular scabies. Sixty eight patients suffering from nodular scabies and twenty apparently healthy subjects as control group were included .The mean age of patients group was ( 31.67±1.67)years compared with (33.5 ±2.27) years in control group .Among patients group, males represent(76.5%) compared with (23.5%) females. Among control group males represent (55%) versus (45%) females .The mean of IgE concentration among control group was (59.25 ± 5.36 U/ml) compared with (160.16 ±16.78 U/ml )among patients group with statistical significant difference (p>0.05 ).In (34/ 68) of scabietic patients, the concentration of IgE was lower than cutoff concentration with the mean (46.23 ±5.09IU/ml ).The rest (34/ 68) scabietic patients have elevated concentration of IgE(274.08 ±18.18IU/ml ).There was a statistical significant difference (p>0.05) between patients groups in IgE concentrations. This study concludes that the diagnostic value of IgE as a serological marker cannot be considered as a single parameter for diagnosis of nodular scabies without clinical manifestations. This study proved that the serological concentration of IgE not necessarily elevated in all cases of nodular scabies